2010
DOI: 10.1017/s0305000909990560
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive architectures and language acquisition: A case study in pronoun comprehension

Abstract: In this paper we discuss a computational cognitive model of children's poor performance on pronoun interpretation (the so-called Delay of Principle B Effect, or DPBE). This cognitive model is based on a theoretical account that attributes the DPBE to children's inability as hearers to also take into account the speaker's perspective. The cognitive model predicts that child hearers are unable to do so because their speed of linguistic processing is too limited to perform this second step in interpretation. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 30 publications
3
75
0
Order By: Relevance
“…We expect that more cognitive effort is needed when processing a pronominal subject or object compared to a non-ambiguous subject NP or reflexive object (cf., e.g. Hendriks, Van Rijn, & Valkenier, 2007;Van Rij, Van Rijn, & Hendriks, 2010;Van Rij et al, 2013), a difference that should be reflected in fewer topic-continuation interpretations in referent selection and in longer response times (RTs).…”
Section: Introductionmentioning
confidence: 99%
“…We expect that more cognitive effort is needed when processing a pronominal subject or object compared to a non-ambiguous subject NP or reflexive object (cf., e.g. Hendriks, Van Rijn, & Valkenier, 2007;Van Rij, Van Rijn, & Hendriks, 2010;Van Rij et al, 2013), a difference that should be reflected in fewer topic-continuation interpretations in referent selection and in longer response times (RTs).…”
Section: Introductionmentioning
confidence: 99%
“…Van Rij, van Rijn and Hendriks (2010) found that the classification of children into different subgroups (based on task performance) was predictive of their linguistic behavior.…”
Section: Classification Into Subgroupsmentioning
confidence: 99%
“…Chien & Wexler, 1990). A yes-bias results in above chance performance on match items but below chance performance on mismatch items (see van Rij et al, 2010, for discussion and a computational account of the yes-bias). No other effects were significant.…”
Section: Incorrect Performance Groupmentioning
confidence: 99%
See 2 more Smart Citations